Hadith as Legal Basis in Judicial Decisions: Examining The Application of Hadith in Child Custody Cases at The High Religious Court of Surabaya - Jamaluddin Malik, Arif; Soleh Kurniawan, Cecep (Fakultas Syariah UIN Sulthan Thaha Saifuddin Jambi, Indonesia, 2025)
Dispute over child custody after divorce is one of the competencies of the religious court. Applying hadith regarding custody regulations as one of the considerations of the decision, if used with a proper understanding of the meaning of the hadith, will result in a decision-oriented to realizing the best interests and benefit of the child. This article aims to explain the meaning of the hadith about custody regulations from the perspective of judges at the Surabaya Religious High Court and its application in decisions on child custody cases. Qualitative data were collected using documentation techniques, questionnaires, and interviews with several judges at the High Religious Court in Surabaya. Seven judges were interviewed. The data collected were then analyzed using descriptive and analytical techniques, incorporating both deductive and inductive approaches. The study results show that applying the custody regulations hadith in the PTA judge's decision regarding child custody matters considers the child's condition so that they continue to receive love from both parents. Thus, there are other meanings in understanding hadith besides those developed by hadith expert scholars, especially in the approach used. Judges strive to achieve the goal of benefiting children by applying careful considerations, not only to hadith, fiqh, and applicable statutory provisions, but with a greater emphasis on the interests and benefits of children. The meaning of these judges is also different from some of the opinions developed in fiqh studies regarding the condition of the children being cared for and the requirements for caregivers. The difference is visible because the realities in the field are not the same as the formulation of the provisions in the books of fiqh.